BATH INDEXES IN THE EVALUATION OF PATIENTS WITH ANKYLOSING SPONDYLITIS - Kamil Yazıcıoğlu; A. Salim Göktepe; Bilge Yılmaz; Şükrü Gündüz (Archives of Rheumatology, 2003)
In this study, we investigated the application of Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Functional Index (BASFI), Bath Ankylosing Spondylitis Global Index (BASGI) and Bath Ankylosing Spondylitis Metrology Index (BASMI) to the Turkish population and the relationship among those indexes. The study was performed in GATA PM&R Department and 128 male patients diagnosed with definite Ankylosing Spondylitis according to 1966 New York criteria. The patients are requested to fill the forms of BASDAI, BASGI and BASFI on a visual analog scale under the supervision of a physician. For metrology index, the physician made the measurements. In the end of the study, metrology index (BASMI) showed no correlation with the disease activity index (BASDAI), whereas the functional index (BASFI) showed a good correlation with both BASMI and BASDAI. In conclusion, patients with Ankylosing Spondylitis need life long follow-up and BASMI, BASDAI, BASFI, and BASGI can be helpful for patient evaluation.